2007
DOI: 10.6026/97320630002057
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a casein kinase II phosphorylation domain in NS1 protein of H5N1 influenza virus

Abstract: Abstract:Influenza virus causes febrile respiratory illness. The infection results in significant mortality, morbidity and economic disruption. In this bioinformatics study, we used the NS1 (the conserved nonstructural) protein of influenza A virus to demonstrate its role in infectivity. Our in silico study revealed a new Casein kinase II (CKII) phosphorylation domain at position 151-154. This domain was formed due to the mutation at position 151 (T151I). Moreover, considerable difference in the secondary stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Changes like that are known to change secondary structure, altering solvent exposure and interactions between proteins. [48][49][50] However, no mutation seemed to induce conformational alterations in the third cytoplasmic loop. The coil structure was maintained in all rare variants.…”
Section: Discussionmentioning
confidence: 99%
“…Changes like that are known to change secondary structure, altering solvent exposure and interactions between proteins. [48][49][50] However, no mutation seemed to induce conformational alterations in the third cytoplasmic loop. The coil structure was maintained in all rare variants.…”
Section: Discussionmentioning
confidence: 99%
“…NS1 and the RNP components including NP are phosphoproteins in various types and strains of influenza viruses (Sanz-Ezquerro et al, 1998;Bui et al, 2002;Arrese & Portela, 1996;Skorko et al, 1991;Marschall et al, 1999;Neumann et al, 1997;Privalsky & Penhoet, 1978, 1981. Several cellular protein kinases, including protein kinase C (PKC), casein kinase II, cyclin-dependent kinases (CDKs) and extracellular signal-regulated kinases (ERKs) were described as candidates for catalysing one or more of these important protein modifications (Anwar & Khan, 2007;Hale et al, 2008b;Neumann et al, 1997). PKC inhibitors were found to exert a block of influenza virus replication, mainly directed to viral entry (Sieczkarski et al, 2003;Root et al, 2000).…”
mentioning
confidence: 99%
“…7 of the potential phosphorylation sites are Casein kinase II (CKII) phosphorylation sites encompassing different region of the protein. One study has previously reported a CKII phosphorylation domain [ 10 ]. 16 of the potential phosphorylation sites are Protein kinase C (PKC) phosphorylation site encompassing different regions of the protein.…”
Section: Resultsmentioning
confidence: 99%